2022
DOI: 10.12973/ijem.8.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Pre-Service Teachers’ Perspectives: Gender and Gender Representation across Human Protagonists in Picture Books

Abstract: <p style="text-align: justify;">Gender is ever present in education preparation, school materials, curriculum, and school systems. To improve our knowledge about different facets of gender and the extent to which the depiction of gender has changed over time in picture books, there is a need to dig beneath the surface of questions about gender representation in picture books. Given that in-service teachers have proximity to approximately 75 million K-12 students, how in-service teachers think about gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(43 reference statements)
0
0
0
Order By: Relevance
“…Numerous studies have demonstrated that picture books may not only naturally and vividly express complex literary ideas, but also help children develop their personalities, artistic aesthetic ability, creativity, and imagination [1][2][3] [4]. As a result, preschool administrators started to enhance the picture book teaching guarantee method.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that picture books may not only naturally and vividly express complex literary ideas, but also help children develop their personalities, artistic aesthetic ability, creativity, and imagination [1][2][3] [4]. As a result, preschool administrators started to enhance the picture book teaching guarantee method.…”
Section: Introductionmentioning
confidence: 99%